Research on multiple improvement paths of national innovation output based on tsQCA - Zhenxing Gong; Xiangge Wang; Miaomiao Li (PLoS ONE, 2025)
Based on the panel data of 118 countries from 2013 to 2024, this paper uses the tsQCA method to explore the synergistic effect of various factors of innovation input on innovation output capacity, and reveals multiple paths to improve national innovation output. The results show that there are four ways to improve the output of high innovation, which can be summarized into two models: “Institution + Human Capital and Research + Business Maturity” and “Infrastructure + Market Maturity + Business Maturity”, among which business maturity is an indispensable core factor for countries to improve their innovation output capacity. In the time dimension, the consistency level of the four high-innovation output configuration pathways in 2019–2020 was low. In the spatial dimension, there are obvious regional differences in innovation output among countries. Among them, there is a considerable gap in innovation output capacity in Africa compared with other regions; Influenced by the process of economic transformation and the pace of institutional improvement, the level of innovation output in Eastern Europe lies between that of Europe and America on one hand and Central and South Asia on the other; Central and South Asia has formed a gradient gap with Europe and America as a whole due to insufficient infrastructure and limited market maturity.